Forecasting the total aggressiveness of the combustion products due sulfur-containing components of pulverized coal - M. S. Ivanitskiy (Известия высших учебных заведений: Проблемы энергетики)
The paper presents the results ofpredicting total aggression of gas emissions of coal-fired boilers, due to sulfur-containing components in the presence of benz(a)pyrene, carbon monoxide, and a minor influence of the nitrogen-containing fuel components on the basis of correlation analysis. For ecological systems "benz(a)pyrene-oxide sulphur", "benz(a)pyrene-carbon monoxide", "sulfur oxide-carbon monoxide" is defined the coefficients of pair correlation. The data for the organization of small-toxic modes of coal-fired boilers taking into account the mutual influence of sulfur-containing components of the flue gases and products of incomplete combustion, allowing a significant degree to ensure environmental safety of the environment.